The emergence of Hindi literature: from transregional Maru-Gurjar to Madhyadeśī narratives - Bangha, I (Oxford University Press, 2018)
Imre Bangha locates the source of what would later become the literary idioms associated with the Hindi heartland—Brajbhasha, Avadhi, Khari Boli, and so on—in Maru-Gurjar, an idiom originating not in the Gangetic plain but in western India, particularly the lands of modern Gujarat and western Rajasthan. Bangha argues that it was this literary language, originally cultivated by Jains beginning in the late twelfth century, that eventually spread to the lands known as madhyadeś, where in the course of the fourteenth and fifteenth centuries it developed into the forms that we now associate with Brajbhasha and Avadhi. Bangha also reveals that the linguistic and literary evidence for this connection has been apparent for some time, but modern Hindi literary historiography, taking nationalism as its organizing principle and embracing a strict sense of religion as one of the significant boundaries of literary culture, has been largely unable to see it.